Accidents of marriage : a novel - Meyers, Randy Susan (Atria Books, 2014)
Maddy is a social worker trying to balance her career and three children. Years ago, she fell in love with Ben, a public defender, drawn to his fiery passion, but now he's lashing out at her during his periodic verbal furies. She vacillates between tiptoeing around him and asserting herself for the sake of their kids, until the rainy day when they're together in the car and Ben's volatile temper gets the best of him, leaving Maddy in the hospital fighting for her life.